INISIASI PROGRAM SAHABAT ANTAR OBAT (SOBAT) DI RUMAH SAKIT UMUM DAERAH WALUYO JATI KRAKSAAN PROBOLINGGO - Hinda Suliati (Najah: Journal of Research and Community Service, 2023)
The "Sahabat Antar Obat" (SOBAT) program is a significant community engagement effort implemented at Waluyo Jati Regional General Hospital in Kraksaan, Probolinggo. The initiative aims to build a supportive network to assist patients in post-discharge medication management. Through a collaborative effort between healthcare professionals, volunteers, and patients, the program facilitated the delivery of medication to the homes of discharged patients. The implementation process includes training sessions for volunteers and patient education on medication adherence. Preliminary results show an increase in medication adherence among patients and a decrease in hospitalization rates. The SOBAT program underscores the potential of community-based interventions in promoting continuity of care and improving post-hospitalization patient experience.